International Models of How to Combine Formal, Non-formal and Informal Education - Petra Bollweg; Hans-Uwe Otto (Social Work and Society)
Landscapes of education are a new topic within the debate about adequate and just education and human development for everybody. In particular, children and youths from social classes affected by poverty, a lack of prospects or minimal schooling are a focal group that should be offered new approaches and opportunities of cognitive and social development by way of these landscapes of education. It has become apparent that the traditional school alone does not suffice to meet this need. There is no doubt that competency-based orientation and employability are core areas with the help of which the generation now growing up will manage the start of its professional career. In addition and by no means less important, the development involves individual, social, cultural and societal perspectives that can be combined under the term of human development. In this context, the Capability Approach elaborated by Amartya Sen and Martha Nussbaum has developed a more extensive concept of human development and related it to empirical instruments. Using the analytic concept of individual capabilities and societal opportunities they shaped a socio-political formula that should be adapted in particular to modern social work. Moreover, the Capability Approach offers a critical foil with regard to further development and revision of institutionalised approaches in education and human development.